Ear acupressure therapy stone and method for manufacturing the same

KR103021774B1Active Publication Date: 2026-09-18황로희
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020260001133
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-01-05
Publication Date
2026-09-18
Estimated Expiration
2046-01-05

Smart Images

  • Figure 112026000947664-PAT00001_ABST
    Figure 112026000947664-PAT00001_ABST
Patent Text Reader

Abstract

A method for manufacturing a qi stone for auricular stimulation therapy according to one embodiment of the present invention comprises: a step of mixing natural mineral raw materials including red clay, white clay, tourmaline, germanium, white porphyritic rock, illite, and pozzolan; a step of adding 10 to 30 parts by weight of water to 100 parts by weight of the mixed natural mineral raw materials and then forming a spherical qi stone precursor; a step of manufacturing a calcined body by calcining the qi stone precursor at a temperature of 1050℃ to 1300℃; and a step of obtaining a qi stone from the calcined body, wherein the qi stone has a diameter of 1.6mm to 1.9mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a stone for auricular stimulation therapy and a method for manufacturing the same. Background Technology

[0002] Auricular stimulation therapy has been widely used as an auxiliary stimulation method to regulate body balance and induce various physiological responses by applying pressure to specific acupoints on the ear. Traditionally, auricular stimulation devices using metal beads, magnetic beads, ceramic beads, etc., have been used and provided in a form that attaches to specific parts of the ear via tape.

[0003] However, conventional auricular stimulation devices are based on metal or single-material structures, so the surface roughness and contact intensity are inconsistent, causing excessive skin irritation and pain.

[0004] Furthermore, conventional auricular acupuncture devices had limitations in the combined application of functional ingredients because it was difficult to adsorb, impregnate, store, or gradually release active ingredients.

[0005] Furthermore, conventional auricular acupuncture devices failed to adequately consider wearability and attachment stability in their size and shape design, resulting in problems such as increased pain, the possibility of detachment, and an increased foreign body sensation.

[0006] In addition, conventional auricular stimulation devices lacked sufficient structural stability and mechanical strength, leading to problems such as cracking and deformation during the firing process or breakage during use.

[0007] Furthermore, existing auricular acupuncture devices had limitations in that hygienic, functional, and physical stability could not be sufficiently ensured because various functional elements, such as far-infrared radiation characteristics, antibacterial properties, surface stability, and thermal buffering performance, were not considered simultaneously. Prior art literature

[65535] Korean Published Patent Application No. 10-2006-0102578 (September 28, 2006) The problem to be solved

[0008] The present invention aims to provide continuous and balanced pressure stimulation to ear acupoints by improving structural stability and surface contact characteristics through the application of a natural mineral-based composite composition and the provision of a porous ceramic structure stone formed through a firing process.

[0009] In addition, the present invention aims to complement and enhance the acupoint stimulation effect by applying a natural mineral-based composite composition having far-infrared radiation characteristics to assist the thermal stimulation environment upon contact with the body surface.

[0010] In addition, the present invention aims to provide a stable user experience upon skin contact by maintaining a hygienic wearing environment on the surface of the stone.

[0011] Furthermore, it is evident that the technical challenges are not limited to those described above, and that other technical challenges may be derived from the following description. means of solving the problem

[0012] A method for manufacturing a qi stone for auricular stimulation therapy according to one embodiment of the present invention comprises: a step of mixing natural mineral raw materials including red clay, white clay, tourmaline, germanium, white porphyritic rock, illite, and pozzolan; a step of adding 10 to 30 parts by weight of water to 100 parts by weight of the mixed natural mineral raw materials and then forming a spherical qi stone precursor; a step of manufacturing a calcined body by calcining the qi stone precursor at a temperature of 1050℃ to 1300℃; and a step of obtaining a qi stone from the calcined body, wherein the qi stone has a diameter of 1.6mm to 1.9mm.

[0013] In addition, the above natural mineral raw material is characterized by comprising 10-25% by weight of red clay, 10-25% by weight of white clay, 8-25% by weight of tourmaline, 3-12% by weight of germanium, 8-20% by weight of white porphyry, 3-12% by weight of illite, and 1-10% by weight of pozzolan.

[0014] In addition, the above natural mineral raw material is characterized by further including 0.1 to 5 weight% of silver antibacterial agent, 1 to 6 weight% of jade, 1 to 6 weight% of cloisonné stone, 1 to 6 weight% of raw ore, and 1 to 6 weight% of sericite.

[0015] In addition, the method is characterized by further including, after the step of obtaining the above-mentioned stone, the step of immersing the above-mentioned stone in an acupuncture solution containing at least one of Angelica gigas extract, Astragalus membranaceus extract, Cnidium officinale extract, Angelica dahurica extract, and Artemisia vulgaris extract.

[0016] A stone for auricular stimulation therapy according to another embodiment of the present invention is characterized by being fired from natural mineral raw materials including red clay, white clay, tourmaline, germanium, white porphyritic stone, illite, pozzolan, silver antibacterial agent, jade, seven-jewel stone, raw ore, and sericite, and being formed into a spherical shape having a diameter of 1.6 mm to 1.9 mm. Effects of the invention

[0017] The present invention has the effect of improving the structural stability and surface contact characteristics of the stone through a porous ceramic structure formed by a composite composition based on natural minerals and a firing process, and stably providing continuous and balanced pressure stimulation when attached to an ear acupoint.

[0018] In addition, the present invention forms a gentle thermal auxiliary stimulation environment upon contact with the body surface due to a natural mineral composition having far-infrared radiation characteristics, and accordingly, the effect of acupoint stimulation is complemented and enhanced through combined action with pressure stimulation.

[0019] In addition, the present invention has the effect of maintaining a hygienic wearing environment on the surface of the stone through a composition having an antibacterial function and a surface stabilization structure, and providing a stable and comfortable user experience even during prolonged skin contact.

[0020] Furthermore, since the effects of the present invention described above are naturally manifested by the composition of the described content regardless of whether the inventor is aware of them, the aforementioned effects are merely a few effects based on the described content and should not be recognized as describing all effects that the inventor has grasped or that actually exist.

[0021] In addition, the effects of the present invention should be further understood from the overall description in the specification, and even if not explicitly stated, if an effect can be recognized as such by a person of ordinary knowledge in the technical field to which the described content belongs through the present specification, it should be considered as an effect described in the present specification. Brief explanation of the drawing

[0022] FIG. 1 is a drawing showing a method for manufacturing a stone for auricular stimulation therapy according to one embodiment of the present invention. Figure 2 is a test report showing the results of the far-infrared radiation characteristics test. Figure 3 is a test report showing the radiation dose. Figure 4 is a test report showing the results of the antibacterial test. Figure 5 is a certificate showing the results of a skin irritation test. Specific details for implementing the invention

[0023] It should be noted that in assigning reference numbers to the components of each drawing in this specification, identical components are given the same number as much as possible, even if they are shown in different drawings.

[0024] Meanwhile, the meaning of the terms described in this specification should be understood as follows. Singular expressions should be understood to include plural expressions unless the context clearly defines otherwise, and terms such as "first," "second," etc. are intended to distinguish one component from another, and the scope of rights should not be limited by these terms. Terms such as "include" or "have" should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.

[0025] The term “at least one” should be understood to include all combinations that can be presented from one or more related items. For example, the meaning of “at least one of the first item, the second item and the third item” is not only the first item, the second item, or the third item individually, but also all combinations of items that can be presented from two or more of the first item, the second item, and the third item.

[0027] FIG. 1 is a drawing showing a method for manufacturing a stone for auricular stimulation therapy according to an embodiment of the present invention. As shown in FIG. 1, the method for manufacturing a stone for auricular stimulation therapy according to the present invention includes the steps of mixing raw materials (S100), molding a stone precursor (S200), manufacturing a calcined body (S300), obtaining a stone (S400), immersing in an acupuncture solution (S500), spraying phytoncide (S600), and drying the stone (S700).

[0028] First, in the step of mixing raw materials (S100), natural mineral raw materials may be mixed. Here, the natural mineral raw materials may include red clay, white clay, tourmaline, germanium, white porphyritic rock, illite, pozzolan, silver antibacterial agent, jade, seven-jewel stone, raw ore, and sericite.

[0029] Loess is a clay-based mineral that imparts plasticity and cohesiveness in the step (S200) of molding the base stone precursor described later, and forms a porous structure after firing in the step (S300) of manufacturing the fired body described later, thereby forming the basic framework (or base matrix) of the base stone.

[0030] This porous structure increases the surface area, thereby improving the surface contact characteristics of the acupoint stone when attached to the ear. Additionally, during the step of immersion in the acupoint solution (S500) described later, it adsorbs the acupoint components to fix them inside the acupoint stone. Furthermore, the porous structure contributes to thermal and mechanical buffering of the internal structure.

[0031] Meanwhile, red clay has traditionally been known as a material that emits far-infrared rays, stabilizes body heat, and aids in the circulation of bodily energy, and has been utilized based on the perception that it is a biocompatible mineral that supports natural healing and purification.

[0032] White clay is a clay-based mineral that improves mechanical strength and dimensional stability after firing in the step (S300) of manufacturing a fired body described later, and maintains the skeletal structure of the base stone homogeneously, thereby supporting the structural stability of the overall composition. In addition, white clay contributes to the formation of a porous structure, thereby improving surface contact and adsorption performance.

[0033] White clay is known to have traditionally been utilized as a mineral material that aids in skin purification, adsorption, and the removal of waste products, and is also known to contribute to the emission of far-infrared rays and the stabilization of the body surface environment.

[0034] Tourmaline is a mineral that is included as a dispersed filler within the pyrotechnic stone to impart surface and electrical and thermal properties, and plays a role in inducing changes in physical properties while maintaining structural stability together with red clay and white clay.

[0035] Tourmaline is widely known as a mineral that emits far-infrared rays and generates microcurrents and negative ions, and these properties are known to help balance the electrical environment of the body surface and harmonize the flow of body energy.

[0036] Germanium is distributed in trace amounts on the surface of the base stone and the particle boundary layer after calcination in the step (S300) of manufacturing the calcined body described later, and acts as an auxiliary component that finely adjusts the surface electrochemical properties and plays a role in complementing the functional properties of the entire composition.

[0037] Germanium has been known to aid in the flow of microcurrents and energy balance within the body by participating in the balance of far-infrared rays and electron transfer, and has been utilized as an auxiliary material for bioenergy regulation.

[0038] Baekbaekbanseok is a porous silicate mineral that supports adsorption and thermal buffering properties, and is included as a dispersed filler in the base stone to improve structural stability and surface interface properties.

[0039] Baekmaekbanseok has traditionally been known to help adsorb and purify impurities and harmful substances and remove turbidity, and has been used as a material that contributes to the balance of bodily and environmental energy through the auxiliary effects of far-infrared rays and mineral wavelengths.

[0040] Illite is a layered clay mineral that supports surface and thermal stability and regulates moisture interface characteristics, thereby improving the adaptability of the base stone to its usage environment.

[0041] Illite has traditionally been widely known as a mineral with antibacterial, deodorizing, and heavy metal adsorption functions, and has been utilized as a material with far-infrared radiation properties along with air purification and environmental improvement effects.

[0042] Pozzolan acts as an auxiliary component in the step (S300) of manufacturing the sintered body described later, assisting in the microstructural bonding during the sintering process and improving the structural stability and bonding strength of the basic framework of the stone through the formation of a glassy phase.

[0043] Pozzolans are traditionally described as auxiliary materials that aid in the enhancement of functionality in complex mineral compositions, playing a role in facilitating energy transfer between minerals and reinforcing structural stability energy.

[0044] The silver antibacterial agent provides antibacterial, deodorizing, and hygienic environment improvement effects by gradually leaching silver ions from the surface or near the pores of the base stone after firing in the step (S300) of manufacturing the calcined body described later.

[0045] In addition, silver antimicrobial agents have traditionally been utilized as hygiene and health supplement materials, as silver ions stabilize the body surface environment and help balance the bioenergy field.

[0046] Jade acts as a relatively stable filler within the base stone, supporting structural reinforcement and thermal mass, and plays a role in complementing the stability and texture of the fired body.

[0047] Jade has traditionally been known to emit far-infrared rays and negative ions, helping to stabilize body temperature and promote blood circulation, and has been used since ancient times as a healing and protective stone to protect bodily energy.

[0048] Chilboseok serves as an auxiliary filler within the base stone, providing surface stability and structural buffering to support the physical properties of the base stone.

[0049] Chilboseok has traditionally been introduced as a material with antibacterial and far-infrared emission properties, and its complex mineral wavelengths are known to help harmonize bodily energy.

[0050] Raw ore acts as an auxiliary filler within the base stone, buffering structural stability and surface properties, and contributing to maintaining the balance of the base stone composition.

[0051] Raw ore is traditionally described as harmonizing the energy environment through complex mineral wavelengths and is utilized as a far-infrared and mineral wavelength reinforcing material.

[0052] Seric mica is a layered mineral with a plate-like structure that functions as a reinforcing filler to inhibit crack propagation and improve dimensional and thermal stability.

[0053] Seric mica has traditionally been utilized as a mineral with energy reflection and wavelength modulation effects, and is known as a material that assists in antimicrobial activity and helps balance environmental energy.

[0054] In one embodiment, the natural mineral raw material may include 10-25% by weight of red clay, 10-25% by weight of white clay, 8-25% by weight of tourmaline, 3-12% by weight of germanium, 8-20% by weight of white porphyry, 3-12% by weight of illite, 1-10% by weight of pozzolan, 0.1-5% by weight of silver antibacterial agent, 1-6% by weight of jade, 1-6% by weight of cloisonné stone, 1-6% by weight of raw ore, and 1-6% by weight of sericite.

[0056] Here, if the content of loess is less than 10% by weight, the binding and plasticity as clay minerals are not sufficiently expressed, making it difficult to maintain the shape of the molded body described later, and increasing the likelihood of pulverization or cracking during the firing and cooling processes.

[0057] In addition, if the content of loess exceeds 25% by weight, the volume change due to moisture shrinkage increases and a porous structure is excessively formed, which may lead to a decrease in mechanical strength and an increase in cracking and plastic deformation.

[0059] If the white clay content is less than 10% by weight, it is difficult to secure strength and dimensional stability after firing, resulting in an uneven skeletal structure and reduced overall structural stability.

[0060] In addition, if the content of white clay exceeds 25% by weight, densification proceeds excessively, the porosity decreases, the function due to the porous structure is reduced, and the dispersion of other filler components is hindered, which may lead to a decrease in the expression of function.

[0062] If the tourmaline content is less than 8% by weight, the functional auxiliary effect as a dispersion filler is weak, and the expected functional characteristics are not sufficiently expressed.

[0063] In addition, if the tourmaline content exceeds 25% by weight, the continuity of the basic framework of the base stone is weakened, and the moldability and sintering stability are reduced, resulting in reduced strength or internal defects.

[0064] When the germanium content is less than 3% by weight, the effect of the trace additive on changing properties is not significant, so the functional contribution becomes practically negligible.

[0065] In addition, if the germanium content exceeds 12% by weight, the likelihood of local concentration or phase separation occurring during the sintering process increases, causing structural non-uniformity and deterioration of physical properties.

[0066] If the content of white porphyritic rock is less than 8% by weight, auxiliary functions such as adsorption and thermal buffering are not sufficiently expressed.

[0067] In addition, if the content of white porcelain exceeds 20% by weight, the porous filler increases excessively, which lowers mechanical strength and causes the matrix structure to become discontinuous, which may impair sintering stability.

[0068] When the illite content is less than 3 weight percent, the surface stability and interface control effects are not practically meaningful.

[0069] In addition, if the illite content exceeds 12% by weight, the proportion of clay components becomes excessive, increasing the likelihood of drying shrinkage and cracking, and may cause structural defects.

[0070] If the pozzolan content is less than 1 weight%, the effects of assisting microstructure bonding and forming a glassy phase during firing are not sufficiently expressed.

[0071] In addition, if the pozzolan content exceeds 10% by weight, an excessive amount of glass is formed, clogging the pores of the stone and causing the structure to become excessively densified, which may lead to increased brittleness and reduced functionality.

[0072] If the content of the antimicrobial agent is less than 0.1% by weight, the amount of silver ions released is insufficient, so the antimicrobial effect is not substantially expressed.

[0073] In addition, if the content of the antibacterial agent exceeds 5% by weight, there is a possibility that aggregation or volatilization may occur during the firing process, and a decrease in mechanical properties and structural non-uniformity may be induced.

[0074] When the jade content is less than 1 weight%, the reinforcing and thermal mass assistance effects do not appear significantly. In addition, if the jade content exceeds 6 weight%, the inert filler increases excessively, leading to increased weight and brittleness, and there is a risk that the sintering homogeneity will decrease.

[0075] If the content of the seven-jewel stone is less than 1% by weight, its function as an auxiliary filler is weak, and the expected auxiliary properties are not sufficiently expressed.

[0076] In addition, if the content of the seven-jewel stone exceeds 6 weight percent, there is an excess of non-functional filler, which may reduce structural continuity and decrease strength.

[0077] When the content of raw ore is less than 1 weight%, the effect of assisting physical properties is not actually significant.

[0078] In addition, if the content of raw ore exceeds 6 weight%, the proportion of inert filler increases, which weakens the matrix structure and may reduce mechanical stability.

[0079] If the sericite content is less than 1 weight%, the crack inhibition and dimensional stability reinforcement effects are not sufficiently exhibited.

[0080] In addition, if the sericite content exceeds 6 weight%, the possibility of layer separation and cracking caused by the stacking of plate-like particles increases, and the structural stability of the sintered body may be reduced.

[0082] Afterwards, in the step of forming the basal stone precursor (S200), 10 to 30 parts by weight of water are added to 100 parts by weight of the mixed natural mineral raw material, and then a spherical basal stone precursor is formed.

[0083] At this time, the stone precursor may have a diameter of 1.2mm-2.5mm or 1.5mm-2.2mm.

[0084] For example, a spherical stone precursor can be formed using a molding machine.

[0085] The step of forming the stone precursor (S200) may further include a step of drying the stone precursor.

[0086] The step of drying the stone precursor may involve drying the stone precursor at room temperature for 12 hours or more. This is to remove residual moisture from the stone precursor to prevent cracking or damage to the fired body during the subsequent firing process.

[0087] Afterwards, in the step of manufacturing a sintered body (S300), the stone precursor is sintered at a temperature of 1050℃ to 1300℃ to manufacture a sintered body.

[0088] At this time, in the step of manufacturing the calcined body (S300), the stone precursor can be calcined at a temperature of 1050°C to 1,300°C, 900°C to 1,450°C, or 800°C to 1,550°C for 16 hours or more, 16 hours to 40 hours, 16 hours to 32 hours, or 16 hours to 24 hours.

[0090] Afterwards, in the step of obtaining the base stone (S400), the base stone can be obtained from the manufactured calcined body.

[0091] Step of acquiring the stone (S400)

[0092] The step of obtaining a base stone (S400) according to the present invention may include a step of cooling a calcined body and a step of selecting the cooled calcined body to obtain a base stone.

[0093] First, in the step of cooling the sintered body, the manufactured sintered body is naturally cooled to obtain a stone. Here, the sintered body may be naturally cooled at room temperature for 16 hours or more, 16 hours to 40 hours, 16 hours to 32 hours, or 16 hours to 24 hours.

[0094] The reason for naturally cooling the sintered body is to form a uniform porous structure within the body and suppress microcracks by slowly cooling it, thereby simultaneously securing far-infrared radiation characteristics and structural stability.

[0095] Subsequently, in the step of selecting the cooled sintered body to obtain the agate, the agate can be obtained by selecting a sintered body with a diameter of 1.6 mm to 1.9 mm from the naturally cooled sintered body.

[0096] Since the stone is used as a component for auricular stimulation therapy that applies continuous local pressure by attaching it to specific acupoints on the ear, the particle size is directly related to the intensity of pressure point stimulation, skin comfort and pain, attachment stability (tape adhesion retention), and whether it interferes with daily life or causes a foreign body sensation.

[0097] Accordingly, if the diameter of the stone is reduced to less than 1.6 mm, the contact surface with the acupoint becomes excessively small, leading to excessive pressure concentration, increased risk of pain, inflammation, and skin damage, and also reduced handling and adhesion stability due to the small size.

[0098] In addition, if the diameter of the stone exceeds 1.9 mm, it does not fit the curvature of the ear surface, so the pressure is dispersed, reducing the stimulating effect, and the protrusion increases, leading to increased aesthetic aversion and foreign body sensation, and an increased risk of falling out.

[0099] Meanwhile, the pore stone according to the present invention has a porous structure (or porous ceramic structure) including micropores formed during the firing process. The pores consist of open pores open on the surface and a network of internal pores continuously formed inside, and due to this porous structure, the pore stone can provide a substantially enlarged effective surface area and a liquid suction path similar to a capillary.

[0100] Subsequently, in the step of immersing in the medicinal solution (S500), the stone is immersed in a natural product-based medicinal solution. Here, the medicinal solution may include Angelica gigas extract, Astragalus membranaceus extract, Cnidium officinale extract, Angelica dahurica extract, and Artemisia vulgaris extract. Additionally, it may further include purple bamboo salt ion water.

[0101] At this time, in the step of immersing in the acupuncture solution (S500), the stone may be immersed in the acupuncture solution for 6 hours or more, 6 hours to 24 hours, or 6 hours to 12 hours.

[0102] In the step (S500) of immersing the stone in the immersion solution, the immersion solution gradually penetrates into the interior along the pore network of the stone and is adsorbed and captured on the pore walls by capillary suction and adsorption action caused by the difference in surface energy.

[0103] When the immersion time is set to 6 hours or more, preferably 6 to 24 hours, and more preferably 6 to 12 hours, the immersion solution does not simply remain on the surface of the stone, but penetrates sufficiently to saturate the internal micropore region, and in the step of drying the stone (S700) described later, as some solvent evaporates during the drying process, the immersion component is fixed and settled on the inner wall of the pore.

[0104] In this way, through the porous structure of the stone, the medicinal components impregnated inside the stone are not rapidly lost to the outside, but can be gradually released due to contact, pressure, or changes in body temperature during use, allowing the medicinal components to act stably and continuously.

[0105] Therefore, the process of immersing the medicinal solution in a stone having a porous structure contributes to improving the storage and retention of the medicinal components.

[0106] In such cases, the injectable component can be stably fixed inside the stone having a porous structure.

[0107] Afterwards, in the step of spraying phytoncide (S600), phytoncide can be sprayed onto the base stone so that phytoncide remains on the surface of the base stone.

[0108] Afterwards, in the step of drying the base stone (S700), the base stone can be naturally dried at room temperature for 7 days or more. In this case, the medicinal components and phytoncides can be stably fixed to the base stone.

[0110] Example 1

[0111] Natural mineral raw materials comprising 10-25% by weight of red clay, 10-25% by weight of white clay, 8-25% by weight of tourmaline, 3-12% by weight of germanium, 8-20% by weight of white porphyritic rock, 3-12% by weight of illite, 1-10% by weight of pozzolan, 0.1-5% by weight of silver antibacterial agent, 1-6% by weight of jade, 1-6% by weight of cloisonné stone, 1-6% by weight of raw ore, and 1-6% by weight of sericite were mixed, and 20 parts by weight of water were added to form a spherical nephrite precursor. Subsequently, the nephrite precursor was fired at a temperature of 1050°C to 1300°C to produce a fired body, and a nephrite was obtained by selecting a fired body having a diameter of 1.6mm to 1.9mm from the fired body. The obtained pyrotechnic stone was immersed in a medicinal solution containing Angelica gigas extract, Angelica gigas extract, Astragalus membranaceus extract, Cnidium officinale extract, Angelica dahurica extract, Artemisia vulgaris extract, and purple bamboo salt ionized water, then sprayed with phytoncide, and the pyrotechnic stone was naturally dried.

[0113] 1. Far-infrared radiation characteristics test

[0114] The far-infrared radiation characteristics test was performed for Example 1 according to test method KFIA-FI-1005, and the test results are shown in Table 1 below. The far-infrared radiation characteristics test was performed at 37℃, and the results are expressed as measurements relative to BLACK BODY using an FT-IR Spectrometer. Figure 2 is a test report showing the far-infrared radiation characteristics test results.

[0116] Emissivity (5 ~ 20 µm) Radiant energy (W / m² µm, 37℃) Example 1 0.923 3.26 x 10 2

[0117] 2. Radiation Dose Test

[0118] A radiation dose test was performed for Example 1 according to test method KFIA-FI-1108, and the test results are shown in Table 2 below. The radiation dose test was conducted under conditions of an indoor temperature of 25°C and a humidity of 50%, and the radiation dose was measured and expressed as the radiation dose per hour. As a result, the radiation dose was detected to be 0.03 uSv / hr, which was confirmed to be a very low level and within a safe range. Figure 3 is a test report showing the radiation dose.

[0120] Radiation dose (μSv / hr) Close fit Example 1 0.03

[0121] 3. Antimicrobial test

[0122] The antibacterial test for Example 1 was conducted using Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 6538) according to test method KFIA-FI-1002. The initial concentration, concentration after 24 hours, and bacteriostatic reduction rate were compared in a blank state without the sample and in a state with the sample, and the results are shown in Table 3. Figure 4 is a test report showing the results of the antibacterial test.

[0124] Test items Sample Classification Initial concentration (CFU / ml) Concentration after 24 hours (CFU / ml) Normal reduction rate (%) Antimicrobial test by E. coli Blank 2.3 x 10 5 8.5 x 10 6 - Example 1 < 1.0 x 10 3 99.9 Antimicrobial test by Staphylococcus aureus Blank 1.7 x 10 5 5.8 x 10 6 - Example 1 < 1.0 x 10 3 99.9

[0125] 4. Skin irritation test

[0126] The skin irritation test was commissioned to the Global Medical Research Center and assigned test code GMSA-086-PI-25923.

[0127] The study was completed on a total of 32 subjects (48.406 ± 9.297 years), and a occlusive patch was applied to the subjects' backs for 24 hours. The researchers performed a visual evaluation 1 hour and 24 hours after the patch was removed.

[0128] As a result of the test, no skin reaction to the stone was observed in any of the subjects 1 hour and 24 hours after patch removal, and the skin irritation index was 0.00, which was determined to be in the low-irritation category.

[0129] Figure 5 is a certificate showing the results of a skin irritation test.

[0131] The auricular stone for auricular stimulation therapy according to the present invention is attached to an acupoint on the ear using tape to stimulate the acupoint, thereby providing continuous and balanced pressure stimulation to the corresponding area. Accordingly, the operational stability of the acupoint stimulation is improved, and the stimulation effect can be exerted more efficiently. Furthermore, due to the structural and physical characteristics of the auricular stone for auricular stimulation therapy according to the present invention, the sensation of foreign objects is reduced when worn, and the stimulation characteristics can be maintained even during prolonged use.

[0132] Those skilled in the art to which the present invention pertains will understand that the above-described invention may be implemented in other specific forms without altering its technical concept or essential features.

[0133] Therefore, the embodiments described above should be understood as illustrative in all respects and not limiting. The scope of the invention is defined by the claims set forth below rather than by the detailed description above, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the invention.

Claims

Claim 1 A step of mixing natural mineral raw materials including red clay, white clay, tourmaline, germanium, white porphyritic stone, illite, pozzolan, silver antibacterial agent, jade, seven-jewel stone, raw ore, and sericite; a step of adding 10 to 30 parts by weight of water to 100 parts by weight of the mixed natural mineral raw materials and then forming a spherical nebula precursor; a step of producing a sintered body by firing the nebula precursor at a temperature of 1050℃ to 1300℃; a step of naturally cooling the sintered body at room temperature for at least 16 hours to obtain a nebula having a porous ceramic structure including open pores on the surface and a continuously formed pore network inside, and having a diameter of 1.6mm to 1.9mm; and the method comprises the step of immersing the above-mentioned base stone in an acupuncture solution comprising Angelica gigas extract, Astragalus membranaceus extract, Cnidium officinale extract, Angelica dahurica extract, Artemisia vulgaris extract, and purple bamboo salt ionized water for 6 to 24 hours, wherein the acupuncture solution penetrates into the interior along the pore network of the porous ceramic structure, is adsorbed and fixed to the pore walls, and is gradually released during use, and the natural mineral raw material comprises 10-25 wt% red clay, 10-25 wt% white clay, 8-25 wt% tourmaline, 3-12 wt% germanium, 8-20 wt% white porphyritic stone, 3-12 wt% illite, 1-10 wt% pozzolan, 0.1-5 wt% silver antibacterial agent, 1-6 wt% jade, 1-6 wt% seven-treasure stone, 1-6 wt% raw ore, and 1-6 wt% sericite, and after the immersion step, with respect to the base stone in which the acupuncture solution has penetrated A method for manufacturing a qi stone for auricular stimulation therapy characterized by not performing an additional calcination process. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 A natural mineral raw material comprising 10-25 wt% red clay, 10-25 wt% white clay, 8-25 wt% tourmaline, 3-12 wt% germanium, 8-20 wt% white porphyrito, 3-12 wt% illite, 1-10 wt% pozzolan, 0.1-5 wt% silver antibacterial agent, 1-6 wt% jade, 1-6 wt% seven-treasure stone, 1-6 wt% raw ore, and 1-6 wt% sericite is calcined at 1050℃ to 1300℃ and then naturally cooled at room temperature for at least 16 hours to form a porous ceramic structure having a spherical shape with a diameter of 1.6 mm to 1.9 mm and including open pores on the surface and a continuously formed pore network inside, and an acupuncture ingredient comprising Angelica gigas extract, Astragalus membranaceus extract, Cnidium officinale extract, Angelica dahurica extract, Artemisia vulgaris extract, and purple bamboo salt ionized water is said to be formed by the natural mineral raw material A stone for auricular stimulation therapy, characterized by being adsorbed and fixed to the inner walls of the pores of the porous ceramic structure without an additional firing process after the porous ceramic structure is formed by firing and natural cooling, and having phytoncide remaining on the surface.

Citation Information

Patent Citations

  • A far infrared ray radiation heating plate and method of preparing thereof

    KR101051130B1

  • Method of manufacturing solution for intercepting the pulsation of groundwater and emitting far infrared ray to obtain a material for removing toxic substances from user's body

    KR1019990071051A

  • Ceramic Compounds and Manufacture Method of WallFinishing Moltar and Thin Applier by Using NaturalMineral Powders

    KR1020050111051A

  • Method for use for producing seramic ball using tourmaline

    KR1020060102578A